2022
DOI: 10.3390/ijms23137368
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in SARS-CoV-2 Infection and Acute Kidney Injury

Abstract: Vitamin D has been described as an essential nutrient and hormone, which can cause nuclear, non-genomic, and mitochondrial effects. Vitamin D not only controls the transcription of thousands of genes, directly or indirectly through the modulation of calcium fluxes, but it also influences the cell metabolism and maintenance specific nuclear programs. Given its broad spectrum of activity and multiple molecular targets, a deficiency of vitamin D can be involved in many pathologies. Vitamin D deficiency also influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 128 publications
1
6
0
Order By: Relevance
“…To interpret another reason, we can point to the effect of vitamin D in the hampering of leukocytes' adhesion to the endothelium (16). In one review article, Hsieh et al explained the role of vitamin D in the AKI and COVID-19 and supported our hypothesis (10).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…To interpret another reason, we can point to the effect of vitamin D in the hampering of leukocytes' adhesion to the endothelium (16). In one review article, Hsieh et al explained the role of vitamin D in the AKI and COVID-19 and supported our hypothesis (10).…”
Section: Discussionsupporting
confidence: 57%
“…To the best of our knowledge, few studies examined the relationship between vitamin D deficiency and AKI in COVID-19 patients, and their results were inconsistent (10,11). The current study aimed to assess whether the vitamin D3 level at the beginning of hospitalization in COVID-19 patients was correlated to AKI.…”
Section: Discussionmentioning
confidence: 96%
“…A recent casecontrol study revealed that severe COVID-19 can be associated with ED in healthy individuals as a complication, even after their recovery [29]. The long-term consequences on erectile function in men with COVID- 19 are not yet well understood [30]. To the best of our knowledge, only one study showed the presence of viral particles in perivascular erectile tissue, as well as lower protein expression for eNOS in comparison to specimens from men without COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…Current evidence suggests that high levels of suPAR are probably a risk factor for AKI in patients with COVID-19 [18] and this AKI may be related to vitamin D status [168]. Clinically, higher levels of suPAR are linked to a rapid deterioration of renal function in children with CKD [169].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vitamin D is comparatively inexpensive, safe, and widely available. Therefore, supplementation could be considered in these high-risk groups, especially in patients with AKI [53,168]. However, well-designed research is needed to better explore the possible linkage between vitamin D deficiency and COVID-19 morbidity and mortality, and to assess whether the correction of this deficiency can avoid or lessen the severity of COVID-19-related AKI.…”
Section: Discussionmentioning
confidence: 99%